Análise de ilhas de calor diagnosticas por meio de transectos móveis em Assis, Cândido Mota, Maracaí e Tarumã (SP) - Gislene Figueiredo Ortiz Porangaba; Margarete Cristiane de Costa Trindade Amorim (Confins)
In the present article, we aim to analyze the intensity and distribution of heat islands in Assis, Cândido Mota, Maracaí and Tarumã, cities of medium and small size of the countryside in the state of São Paulo, Brazil. Therefore, the technique used was the mobile transects, which consists of recording air temperatures with sensors fitted on the side of vehicles in low travel speed, in the interurban environments and rural surroundings, near built-up areas. Such records took place on the 21st and 22nd of May, on the 3rd to the 6th of June and on the 16th to the 20th of July 2013, at 6 a.m. and 9 p.m., simultaneously, in the four cities. The results showed that Assis, the largest city in the study, had the highest absolute temperature (21.3°C at 06 a.m. and 24.8°C at 9 p.m.) and the highest heat island intensity was observed in Cândido Mota, with 6.7°C at 9 p.m., on July 17th 2013.